Effects of mental fatigue on isometric mid-thigh pull performance and muscle activities - Hyung Suk Yang; Lee T. Atkins; C. Roger James (PLoS ONE, 2025)
This study investigated the effects of mental fatigue on rate of force development (RFD) and peak force during an isometric mid-thigh pull (IMTP), as well as its impact on muscle activation measured by electromyography (EMG) median frequency. Sixteen healthy, resistance-trained males completed two sessions: a control condition and a mentally fatigued state induced by a 30-minute modified Stroop task. IMTP performance and muscle activation were assessed before and after the mental fatigue task. Mental fatigue significantly reduced RFD in the later phase of force generation, specifically within the 20%-80% of maximum force interval (RFD2080) (p =  0.022, d =  0.638). In contrast, no significant changes were observed in RFD within the initial 0-100 milliseconds (RFD100) or 0-200 milliseconds (RFD200) of contraction, nor in peak force. Additionally, mental fatigue led to a significant increase in EMG median frequency for the rectus femoris during the initial 0-1 second interval (p =  0.040, d =  -0.609), with no significant changes in the medial gastrocnemius or other time intervals. These findings suggest that mental fatigue primarily impacts the later stages of force development, affecting the ability to sustain and develop force over time without compromising peak force. The increase in EMG median frequency for the rectus femoris indicates a possible compensatory response to mental fatigue, underscoring the complex influence of cognitive stress on neuromuscular function. This study highlights the importance of considering mental fatigue in activities requiring sustained or progressively increasing force production.